LEGAL CERTAINTY IN THE IMPLEMENTATION OF ECONOMIC ANALYSIS OF LAW FOR POLICY MAKING PROCESS - Maria Grasia Sari Soetopo (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Economic Analysis of Law (EAL) is a method that uses concepts and theories from economics to evaluate the process, formation, structure, and the impact of law on society. The method is implemented through the use of Regulatory Impact Analysis (RIA) as outlined in Law No. 13 of 2022 concerning the Second Amendment Law No. 12 of 2011 concerning the Formation of Legislation (Law No. 13 of 2022). The Law, however, is not supported by implementing regulations explaining how RIA is carried out. This article uses a normative legal research method. The analysis is carried out through both statutory and historical approaches. The results of this research show that the implementation of EAL following the enactment of Law No. 13 of 2022 needs to be supported with various policies, such as issuance of implementing regulations explaning the procedures of conducting RIA in the regulatory making process. These efforts should also be supported by adequate infrastructure facilitated by Ministries and/or Institutions in conducting impact analysis and augmenting skills of policy makers to enchance the development of laws and regulations.